Towards 3D modelling and imaging of infection scenarios at the single cell level using holographic optical tweezers and digital holographic microscopy. Issue 3 (15th June 2012) - Kemper, Björn; Barroso, Álvaro; Woerdemann, Mike; Dewenter, Lena; Vollmer, Angelika; Schubert, Robin; Mellmann, Alexander; von Bally, Gert; Denz, Cornelia
Abstract The analysis of dynamic interactions of microorganisms with a host cell is of utmost importance for understanding infection processes. We present a biophotonic holographic workstation that allows optical manipulation of bacteria by holographic optical tweezers and simultaneously monitoring of dynamic processes with quantitative multi‐focus phase imaging based on self‐interference digital holographic microscopy. Our results show that several bacterial cells, even with non‐spherical shape, can be aligned precisely on the surface of living host cells and localized reproducibly in three dimensions. In this way a new label‐free multipurpose device for modelling and quantitative analysis of infection scenarios at the single cell level is provided. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)